2015
DOI: 10.1371/journal.pone.0138357
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Impairments in Deficit and Non-Deficit Schizophrenia and Their Relationships with Symptom Dimensions and Other Clinical Variables

Abstract: BackgroundDeficit schizophrenia (DS) has been proposed as a pathophysiologically distinct subgroup within schizophrenia. Earlier studies focusing on neurocognitive function of DS patients have yielded inconsistent findings ranging from substantial deficits to no significant difference relative to non-deficit schizophrenia patients (NDS). The present study investigated the severity and characteristic patterns of neurocognitive impairments in DS and NDS patients and their relationships with clinical variables.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 73 publications
3
48
0
1
Order By: Relevance
“…Unfortunately, such relationships have been very rarely examined in this group of patients. Only Yu et al (2015) managed to demonstrate a significant correlation between scores on the TMT and VFT P in patients with DS. It may also be important to identify which aspects of executive function are most impaired in patients with DS and NDS.…”
Section: Introductionmentioning
confidence: 89%
“…Unfortunately, such relationships have been very rarely examined in this group of patients. Only Yu et al (2015) managed to demonstrate a significant correlation between scores on the TMT and VFT P in patients with DS. It may also be important to identify which aspects of executive function are most impaired in patients with DS and NDS.…”
Section: Introductionmentioning
confidence: 89%
“…Neuropsychological investigations reported discrepant findings, with some studies reporting a greater impairment in DS than in NDS on measures of fronto-parietal functions (i.e., attention, executive control and visuospatial functions, Buchanan et al, 1994;Bryson et al, 2001;Yu et al, 2015), prefrontal functions (verbal fluency, concept formation and cognitive flexibility, Cascella et al, 2008;Polgár et al, 2010) or cortico-striatal functions (reinforcement learning, Farkas et al, 2008;Polgár et al, 2010;Vogel et al, 2013). The majority of studies (Galderisi et al, , 2013aWang et al, 2008;Polgár et al, 2008;Réthelyi et al, 2012;Fervaha et al, 2015a) and a meta-analysis (Cohen et al, 2007) reported a generalized cognitive impairment in DS vs both NDS and controls.…”
Section: Neurocognitive Impairmentmentioning
confidence: 99%
“…Firstly, objective neurocognitive deficits in schizophrenia comprise impairments in planning, context processing, working memory, conscious recollection, attention, and visual memory deficits. [8][9][10] Using the Consortium to Establish a Registry for Alzheimer Disease (CERAD) and Cambridge Neuropsychological Test Automated Battery (CANTAB) tests, it was shown that individuals with deficit schizophrenia have more profound and a broader range of cognitive impairments than patients with nondeficit forms of the disorder, including impairments in emotional recognition, semantic and working memory, sustained attention, and especially in episodic memory, including recall and recognition. 10 Secondly, many individuals with schizophrenia experience clinically meaningful depression and anxiety symptoms.…”
Section: Introductionmentioning
confidence: 99%